2022
DOI: 10.1111/eva.13441
|View full text |Cite
|
Sign up to set email alerts
|

Co‐evolutionary adaptations of Acinetobacter baumannii and a clinical carbapenemase‐encoding plasmid during carbapenem exposure

Abstract: OXA-23 is the predominant carbapenemase in carbapenem-resistant Acinetobacter baumannii. The co-evolutionary dynamics of A. baumannii and OXA-23-encoding plasmids are poorly understood. Here, we transformed A. baumannii ATCC 17978 with pAZJ221, a bla OXA−23 -containing plasmid from clinical A. baumannii isolate A221, and subjected the transformant to experimental evolution in the presence of a subinhibitory concentration of imipenem for nearly 400 generations. We used population sequencing to track genetic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 96 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…One interesting observation was the presence of two copies of the bla OXA-23 gene in the oxf ST1114/1841 and oxf ST231 strains. A previous study by Zhang and colleagues reported the duplication of a plasmid-borne bla OXA-23 gene in an A. baumannii strain in the presence of subinhibitory concentrations of carbapenem ( 46 ). This duplication was reported to confer improved fitness in carbapenem-containing media but was also associated with a fitness cost in antibiotic-free media.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting observation was the presence of two copies of the bla OXA-23 gene in the oxf ST1114/1841 and oxf ST231 strains. A previous study by Zhang and colleagues reported the duplication of a plasmid-borne bla OXA-23 gene in an A. baumannii strain in the presence of subinhibitory concentrations of carbapenem ( 46 ). This duplication was reported to confer improved fitness in carbapenem-containing media but was also associated with a fitness cost in antibiotic-free media.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting observation was the presence of two copies of the bla OXA-23 gene in the ST1114/1841 and ST231 strains. A previous study by Zhang and colleagues reported the duplication of a plasmid-borne bla OXA-23 gene in an A. baumannii strain in the presence of sub-inhibitory concentrations of carbapenem 63 . This duplication was reported to confer improved fitness in carbapenem-containing media but was also associated with a fitness cost in antibiotic-free media.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, statistically significant changes in resistance to β-lactam antibiotics (ampicillin/sulbactam), aminoglycosides (amikacin and gentamicin), carbapenems (meropenem and imipenem) and a folate metabolism inhibitor (trimethoprim/sulfamethoxazole) were observed in this member. These resistances are typically conferred by the presence of mobile genetic elements, where conjugative plasmids carrying genes coding for carbapenemases play an important role in the dissemination of carbapenem resistance [50][51][52].…”
Section: Discussionmentioning
confidence: 99%